Innovation capabilities and human development competitiveness in education sector: Evidence from UAE - Al Dulaimi, Ashraf M. Zedan; Al Marzooqi, Sultan Mohamed; Lubis, Asmuliadi; Siren, Norrodzoh Binti Hj; Kassim, Sayyid Buhar (Frontiers in Psychology, 2022)
Innovation capabilities and human development in education sector is one of the key focused areas in United Nations Sustainable Development Goals. The current research is novel to integrate and address such constructs in single theoretical framework. Grounded in Human Capital Theory, this study aims to investigate the role of innovation capabilities in human development competitiveness in the education sector of UAE. Based on the qualitative research approach, data were collected through interviews with 70 experts and leaders working in this field of Human Development Index (HDI) and innovation development in the UAE in order to more comprehensively recognize the main dilemmas involved in the phenomenon under investigation. Results indicate a huge potential of growth and improvement in education sector of UAE for supporting country SDG goals. Furthermore, it applied the conceptual statistics of key performance indicators (KPIs) collected to analyze the UAE’s HDI, innovation capabilities, and human development competitiveness from 2014 to 2020. Results revealed insightful lessons for policymakers and scholars working in innovation management and sustainable development goals area. Especially, this research will bring key policy directions and future research avenues for better innovative capabilities development in the education sector in developing and low-income economies.